Mass transfer and biochemical reaction in immobilized cell packed bed reactors: correlation of experiment with theory - Nath, Sunil; Chand, Subhash (John Wiley & Sons Inc., 2008)
A quantitative analysis of mass transfer combined with biochemical reaction and correlation of experiment with theory is carried out for immobilized cell packed bed reactors for the first time. Experimental data on flow rates and pseudo first-order rate constants, k(ps) for the continuous bioconversion of sugars to ethanol in an immobilized cell reactor using Saccharomyces cerevisiae cells on activated bagasse chips has been analyzed and compared with theory. Theoretically, first-order reaction kinetics was considered and various external film diffusion models of the type j(D) = K Re(-(1-n)) evaluated. The effects of external film diffusion in immobilized cell reactors have been quantified. Various mass transfer correlations were systematically tested and the mass transfer correlation j(D) = 5.7 Re-0.59 correctly predicted experimental data. Use of this correlation is recommended to quantify external film diffusion effects for the continuous bioconversion of sugars to ethanol in immobilized cell packed bed reactors. Finally, the mass transfer coefficient, k(ps) was calculated as a function of the mass velocity, G, and the Reynolds number, Re. This study will be of use in making realistic engineering estimates of the effect of external mass transfer on the observed reaction rates in immobilized cell bioreactors.